PENGARUH LITERASI SEJARAH TERHADAP MINAT BELAJAR SISWA PADA MATERI SEJARAH KEBUDAYAAN ISLAM DI SMAN 1 CANDUNG - Ahmad Khair Simanjuntak; Yulia Rahman (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2025)
The problems faced in Islamic Religious Education lessons on the material of Islamic cultural history at SMAN 1 Candung are the lack of students' desire to learn during History lessons, the lack of students' reading repetition skills is the background of the research carried out. This study uses a quantitative correlational research type. The aim is to see the relationship between variables. Based on the results of the hypothesis test, it is known that Signy <0.05 (0.000 <0.05) for t count> t table (5.178> 1.677) then it can be concluded that Ha is accepted and Ho is rejected, namely the variable of History literacy has an effect on the variable Y of interest in learning. The magnitude of the influence of History literacy on interest in learning can be seen from the Beta value, which is 0.591 x 100% = 59.1%, so it can be seen that the influence caused by literacy on students' desire to learn History material at SMAN 1 Candung is 59.1%. Historical literacy is an important ability that has a major influence in increasing interest in learning the history of Islamic civilization. Therefore, historical literacy needs to be improved through several steps, including: 1) Getting used to reading books at the beginning of learning. Example: Encouraging students to love reading activities outside of class hours, both reading textbooks and non-textbooks. This is important because students tend to listen to teachers explaining material more often than reading and seeking information about history themselves. 2) Developing Students' Conceptual Understanding This step aims to provide an initial basis for students to connect events, causes, and effects. For example, students can be given the task of finding the causes and effects contained in the story of the Wali Songo in the spread of Islam in Java using reliable references. These efforts are expected to help increase students' interest in learning history.